THE RESEARCH LANDSCAPE ON ARTIFICIAL INTELLIGENCE AND ITS RELATIONSHIP WITH E-RECRUITMENT: SYSTEMATIC LITERATURE REVIEW AND FUTURE RESEARCH AGENDA - Mudliar, Ajay Nandakumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Purpose – The objective of this study is to conduct a comprehensive analysis of the current body of existing literature on Artificial Intelligence and its relationship with recruitment. Additionally, this study identifies and emphasize the future research agenda and emerging trends within state-of-art. Design/methodology/approach ¬¬¬¬- A thorough investigation was conducted on a set of 84 publications sourced from the Scopus database spanning the years 2012 to 2023, utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) methodology. Findings – The findings of the study indicate a taxonomical impression of prevailing scientific research on role of Artificial Intelligence in facilitating E-recruitment. Originality/value - This study utilizes Systematic Literature Review to examine literature on aiming to develop a systematic comprehension of the research field of Artificial Intelligence. This study makes a valuable contribution to the current scholarly discourse and provides support for future scholars in their investigations.